Dynamic response of laminated structures using a Refined Zigzag Theory shell element. (1st January 2017) - Treviso, Alessandra; Mundo, Domenico; Tournour, Michel
Abstract: Shell-like structures are common in many engineering applications and composite materials and laminated sandwich are being used as a viable lightweight alternative to standard engineering materials. Simulations of multilayer structures often require explicit modelling in the through-the-thickness direction to account for properties discontinuities, especially sandwich structures, with soft viscoelastic layers, with significant increase in computational time. Reduction of both modelling and computational costs can be achieved by the use of Zigzag theories. The Refined Zigzag Theory (RZT) proposed by Tessler is hereby used in the framework of a shell element for vibration analysis of standard laminates and laminated sandwich structures. The RZT element is then combined with draping simulations to assess its accuracy and performance in the case of double curvature geometries. The main objective of the paper is to show how the RZT element can be effectively used to reduce the computational costs of dynamic simulations and can be successfully combined to other CAE technologies to increase the overall level of accuracy at a reasonable computational cost.